2019
DOI: 10.1186/s12890-019-0959-7
|View full text |Cite
|
Sign up to set email alerts
|

Perception of asthma control among asthmatics seen inChest Clinic at Tertiary Hospital, Addis Ababa, Ethiopia

Abstract: BackgroundPatient awareness of asthma severity is important for optimal asthma management. However, there is often a discrepancy between physician assessment of asthma control based on guidelines and patient discernment of control. We compared physician and patient perception of asthma control in a clinic population seen at a tertiary hospital in Addis Ababa, Ethiopia.MethodsIn this cross-sectional study, 182 consecutive patients with a physician diagnosis of asthma seen in Chest Clinic at Tikur Anbessa Specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…reported by Fenta et al [20] to 75.8.2% reported by Gebremariam [22]. The reason for these variations could be due to the types of diagnotic tools and assessment methods.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…reported by Fenta et al [20] to 75.8.2% reported by Gebremariam [22]. The reason for these variations could be due to the types of diagnotic tools and assessment methods.…”
Section: Discussionmentioning
confidence: 96%
“…Low monthly income, presence of comorbidities, moderate persistent asthma, severe persistent asthma, and use of SABA alone as anti-asthmatic medication [21]. Use of biomass fuel for cooking, longer duration of asthma (>30 years), incorrect inhalation technique, and asthma exacerbation in the last 12 months [22]. Self-perceived poor asthma control was associated with any activity limitation due to asthma and inconsistent inhaled corticosteroid use [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies from Nigeria have reported 82.9% [ 32 ] inadequately controlled asthma. Democratic Republic of Congo (DRC) 56% [ 33 ], the North Africa countries 71.3% [ 34 ] and Ethiopia, Addis Ababa 53.3%-75.8% [ 14 , 35 ] and Jimma 76.1% [ 36 ] have reported uncontrolled asthma. The results of the previous reports were higher than the current finding, which might be explained by the previous studies' findings that enrolled large sample size, studied over an extended duration along with different study settings.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma control and its determinants vary from practice setting as environmental, socio-demographic, medication adherence and availability, and household factors differ significantly across settings [ 13 , 14 , 29 ]. Previous work in Ethiopia, showed that in a tertiary hospital in Addis Ababa a third of adult asthmatics had poor asthma control [ 30 ]. However, there are limited data on childhood asthma control from low-income countries including Ethiopia.…”
Section: Introductionmentioning
confidence: 99%